Numerical simulation for the problem of dynamics of oxide film growth in semiconductor substrates on the basis of geometrical approach and the Deal-Grove method - Alexandrov, A.L.; Tarnavsky, G.A.; Shpak, S.I.; Gulidov, A.I.; Obrecht, M.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2001)
An approximate simulation for the dynamics of oxide film growth in semiconductor substrates is developed. A generalization of the 1D Deal-Grove method to 2D problems is proposed on the basis of geometrical approach. Some numerical results are given for the following cases: 1) the growth of a subregion for SiO2 under oxidation in various mediums (O2 or H2O) and 2) the dynamics of oxide/material and oxide/oxidant boundaries in a wide range of constitutive parameters and nitride masks covering a part of the silicon surface.